PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA APARATUR NAGARI DALAM PENGELOLAAN KEUANGAN NAGARI DI KABUPATEN TANAH DATAR - Mutia Reni (Politeknik STIA LAN Makassar, 2019)
The purpose of study was to analyze the influence of organizational culture on the performance of nagari government apparatus in managing nagari financial in tanah datar regency. Background of this study was still poor performance of nagari government apparatus in managing nagari financial that there was in Tanah Datar Regency. This study used quantitative method. This study was conducted to 75 nagari government in Tanah Datar Regency with total population as many as 600 people consisted of walinagari, nagari secretary, nagari treasurer, and five head of nagari affairs. The sample in this study consisted of 248 respondents determined with slovin formula. The data of this study collected through questionnaire with likert scale measurement. Data of this studi were analyzed with Multiple Linear Regression Test. The result in this study showed that organization culture variabel, both simultaneously and partially significantly influence the nagari financial management in Tanah Datar Regency